A naturally occurring 31 bp deletion in TEOSINTE BRANCHED1 causes branched ears in maize - Ling Ai; Ju Qiu; Jiuguang Wang; Mengya Qian; Tingting Liu; Wan Cao; Fangyu Xing; Hameed Gul; Yingyi Zhang; Xiangling Gong; Jing Li; Hong Duan; et al. (Journal of Integrative Agriculture)
The female inflorescence, or ear, of maize develops no branch meristem (BM), which differs from the male inflorescence, or tassel. While the mutations of some well documented genes, such as fea2/3/4 and ramosa1/2/3, can cause the branched architecture of ears in maize, such mutations also change the normal phenotypic performance of the tassels. In the present study, a natural maize mutant with branched ears, named branched ear1 (be1), was characterized. be1 shows several branched ears at the base of the central ear with unchanged architecture of the tassels. Besides, both the branched and central ears of be1 possess regularly arranged kerels. The phenotypic characteristics of be1 differ completely from those reported mutants of fasciated ears or RAMOSA-like ears in maize. An SEM survey at the very early development stage showed that meristems with three protrusions, similar to the BM in tassels, were present during the development of the branched ears in be1. Gene mapping and sequence alignment suggested that TEOSINTE BRANCHED1 (TB1) was the candidate gene of BE1. Further verification showed that a be1-specific 31 bp deletion at the downstream of BE1 led to statistically reduced expression of this gene in the immature ear, which serves as the potential causal reason for the branched ears of be1. CRISPR/Cas9-based gene editing downstream of TB1 complemented the phenotypic architecture of branched ears, suggesting that TB1 was the target of BE1, and it was named as ZmTB1be1. The results of the present study implied a novel function of TB1 in female inflorescence development, rather than shaping the plant architecture in maize. Meanwhile, further functional dissection of ZmTB1be1 might shed new light on TB1, the most famous domestication related gene in maize.